Digital Branding of Mafia Pentol Through Tiktok - Firdaus, Muhammad Allan; Dharma, Ferry Adhi (Procedia of Social Sciences and Humanities, 2024)
This research aims to explore Mafia Pentol's digital branding strategy comprehensively to increase brand awereness and brand loyalty. By using a qualitative research method that focuses on TikTok social media. The subjects in this study consisted of six people consisting of the owner, the marketing team, the creator team, and TikTok Mafia Pentol followers, while the object of this research is TikTok Mafia Pentol @teammafiapentol.sub. This research was analyzed using the concepts of digital branding and marketing communication. The results of this study state that Mafia Pentol has successfully built a strategy using the TikTok platform to increase brand awareness and brand loyalty. Mafia Pentol conducts market research to understand the competition and identify the right branding strategy. By analyzing the content and trends that are developing on TikTok, Mafia Pentol succeeds in creating content that is interesting and relevant to their audience. Through various digital branding strategies such as maximizing the use of social media, using quality marketing content, and inviting creators to collaborate, they have succeeded in increasing brand awareness of the Mafia Pentol brand. In addition, Mafia Pentol also maintains customer loyalty by actively interacting through social media or directly so that it creates an emotional bond, making this brand widely recommended by consumers to their closest people.